FACTORS OF THE EFFICIENCY OF THE STUDENT LOAN SYSTEM IN LITHUANIA - Bikulčiūtė, Rūta; Želvys, Rimantas (Acta Paedagogica Vilnensia, 2015)
The development of mass higher education caused an austerity of state financing since the middle of the 20th century and encouraged higher education institutions to search for alternative sources of funding. One of the most convenient ways of diversifying the financial resources was the introduction of tuition fees. In this context, the student loans became an attractive means to ensure access to higher education. Student loans gave the students the possibility to cover their tuition fees and living costs and at the same time enabled the governments to save money. It is widely recognized that the higher education provides significant benefits to an individual. Students who are receiving loans get funding for the investment in education, and these loans must be repaid after graduation when the students get their economic benefits. The student loan system of Lithuania is also relevant in the light of the higher education funding model. The article provides an overview of the development of the student loan systems, an analysis of specific objectives of student loan schemes, and the factors influencing these objectives. The analysis of theoretical literature shows that the objectives of student loan systems are the following: improving access to higher education and the financial stability of the sector of higher education, promoting students’ mobility and financial independence, meeting specific manpower needs. The success of the implementation of these objectives depends on the proper model of the student loan system and the national impact.